The Threat of Asymmetric War Against The Border Area (Study of East Kalimantan As The Capital City of The Archipelago) - Yuliana Anggun Pertiwi; Pujo Widodo; Priyanto Priyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The border area of a country is a manifestation of its sovereignty. Security in border areas becomes a challenge for every country because the border area is generally a space for the development of asymmetric warfare threats, especially in its position as the National Capital. East Kalimantan is a manifestation of Indonesia's border area that has the potential to face complex asymmetric warfare threats. This research is a qualitative study aimed at analyzing the forms of asymmetric warfare threats to East Kalimantan as a border area and the National Capital. Based on the research, it is concluded that East Kalimantan is a strategic border area with complex security risks. This area is characterized by actual and potential asymmetric warfare threats ranging from local to transnational scales, such as local conflicts, transnational crimes, and terrorist threats. Threats to East Kalimantan at least have an impact on national security, both directly and indirectly. Therefore, the threats in East Kalimantan need to be a shared concern, given that security gaps in border areas are vulnerable to being exploited by asymmetric actors to present threats.